Establishment Of A General Election Court System In Indonesia - Rayendra Erwin Moeslimin Singaruju (Universitas Islam Indonesia, 2022)
General election disputes in Indonesia frequently cause political and legal issues. Unfortunately, an established dispute resolution institution is not available. This article aims to address this need by addressing the reasons existing legal policy on general election dispute resolution has not succeeded in resolving general election disputes transparently, accountably, and fairly, and the legal policy design and requirements of an ideal general election court for the future. This was a normative legal study using a statutory, case, and conceptual approach. The results of the study showed that the existing legal policy of general election dispute resolution has not been manifested as a strong and stable institution. Two courts, namely the Supreme Court and the Constitutional Court, with different characters and constitutional mandates, alternately have become the forum for resolving general election disputes. The different procedures and decisions between the two courts often negate each other, causing legal uncertainty which ultimately fails to provide justice. In the future, therefore, it is necessary to establish a general election court institution with a special mandate to adjudicate election disputes based on the Election Law to create legal consistency, legal certainty, and fair settlement of election disputes.Keywords: legal policy, elections, dispute resolution, special courts. Pembentukan Sistem Peradilan Pemilihan Umum Di Indonesia Abstrak Sengketa pemilu di Indonesia seringkali menimbulkan masalah politik dan hukum. Sayangnya, lembaga penyelesaian sengketa yang mapan tidak tersedia. Artikel ini bertujuan untuk menjawab kebutuhan tersebut dengan menjawab alasan kebijakan hukum yang ada tentang penyelesaian sengketa pemilihan umum belum berhasil menyelesaikan sengketa pemilihan umum secara transparan, akuntabel, dan adil, dan desain kebijakan hukum dan persyaratan pengadilan pemilihan umum yang ideal untuk masa depan. . Penelitian ini merupakan penelitian hukum normatif dengan pendekatan undang-undang, kasus, dan konseptual. Hasil penelitian menunjukkan bahwa kebijakan hukum penyelesaian sengketa pemilu yang ada belum terwujud sebagai institusi yang kuat dan stabil. Dua pengadilan, yakni Mahkamah Agung dan Mahkamah Konstitusi, dengan karakter dan amanat konstitusi yang berbeda, bergantian menjadi wadah penyelesaian sengketa pemilu. Perbedaan prosedur dan putusan antara kedua pengadilan tersebut seringkali saling meniadakan sehingga menimbulkan ketidakpastian hukum yang pada akhirnya gagal memberikan keadilan. Oleh karena itu, ke depan perlu dibentuk lembaga peradilan pemilu dengan mandat khusus untuk mengadili sengketa pemilu berdasarkan UU Pemilu untuk menciptakan konsistensi hukum, kepastian hukum, dan penyelesaian sengketa pemilu yang adil.Kata kunci: kebijakan hukum, pemilu, penyelesaian sengketa, pengadilan khusus.